First detection of Herpesvirus anguillae (AngHV‐1) associated with mortalities in farmed giant mottled eel (Anguilla marmorata) in Vietnam. Issue 6 (25th March 2021) - Panicz, Remigiusz; Eljasik, Piotr; Nguyen, Tuan Thuc; Vo Thi, Kim Thinh; Hoang, Duat Van
Abstract: Giant mottled eel ( Anguilla marmorata ) farming in Vietnam is a multistage process starting from wild harvest of glass eels through the so‐called "hatcheries" and distribution centres from which individuals are transferred to rearing farms and subsequently sold by one eel farm to another every 3–5 months. The information on viral agents spread and persistence in the Vietnamese eel aquaculture is scarce. Therefore, the mortality of A. marmorata at the Van Xuan Farm was the prerequisite to identify the possible aetiologic agent and additionally to formulate first recommendations for viral disease screening in the Vietnamese eel aquaculture. Juvenile giant mottled eels with haemorrhagic lesions in the skin and liver, and hyperaemia of the gut were tested with qPCR and end‐point PCR for AngHV‐1 presence. Here, we report the first detection of AngHV‐1 associated with mortality in giant mottled eel in winter and spring seasons. On the basis of the obtained results, we recommend to test eel seeds in "hatcheries, " since tropical eel farms operate in interconnected scheme and monitoring of AngHV‐1 prevalence requires well‐implemented measures. Disease screening in the rearing centres and on‐growing facilities should be based on everyday health checks, including by‐catch fish used as a base of the feeding programmes at eel farms in Vietnam.